Strategi Ekspor Kakao Olahan Indonesia melalui International Cocoa Organization (ICCO) ke Uni Eropa - Risnayanti, Niluh Gede; Achmad (UIN ALAUDDIN MAKASSAR, 2024)
Indonesia, as the world's third-largest cocoa producer, joined the International Cocoa Organization (ICCO) in 2012 to improve market access, reduce trade barriers, and strengthen its negotiating position with the European Union in efforts to develop the national cocoa industry and increase exports of processed cocoa to global markets. The aim of this research is to analyze the factors driving Indonesia's joining of ICCO (International Cocoa Organization) and to examine Indonesia's processed cocoa export strategy. This study uses a qualitative approach and descriptive analysis to explore in depth Indonesia's strategy in increasing processed cocoa exports to the European Union through its membership in ICCO. The research results show that Indonesia's joining of the International Cocoa Organization (ICCO) was driven by various strategic factors and followed by the development of a comprehensive processed cocoa export strategy. As a major cocoa producer, Indonesia leverages its ICCO membership to enhance the position and competitiveness of the national cocoa industry in the global market through improved market access, information acquisition, capacity development, and strengthening of diplomatic positions. The export strategy developed includes diplomatic efforts to reduce import tariffs in the European Union, product quality improvement, product diversification and promotion of sustainability certifications. Indonesia actively lobbies, builds alliances with other producing countries, and utilizes ICCO forums for technology transfer.